Water sorption-based thermochemical storage materials: A review from material candidates to manufacturing routes - Palacios, Anabel; Navarro, Maria Elena; Barreneche, Camila; Ding, Yulong (Frontiers in Thermal Engineering, 2022)
A comprehensive and updated review is provided in this article, with a focus on water sorption-based thermochemical storage (WSTCS) materials, covering materials and their manufacturing routes. The state of the art of 22 most relevant salt hydrates is classified into seven groups (bromides, sulphates, carbonates, chlorides, nitrates, hydroxides, and sulphides) and studied as candidates. This is followed by a discussion on TCS material manufacturing, covering both conventional (shaping, pelletizing, etc.) and more advanced routes (e.g., extrusion, 3D printing, encapsulation, etc.). Finally, concluding remarks are presented, including limitations and future potentials for TCS research.